2009
DOI: 10.1080/02652030802368757
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of hydroxythiohomosildenafil in herbal dietary supplements sold as sexual performance enhancement products

Abstract: An unknown compound is detected and isolated from two herbal dietary supplements bought on the internet. The structure of the unknown compound is elucidated using ESI-MS/MS, NMR, UV and IR. The compound, named hydroxythiohomosildenafil, is identified as an analogue of sildenafil in which the oxygen atom is substituted with a sulfur atom in the pyrazolopyrimidine moiety, and a hydroxyethyl group instead of a methyl group is attached to the piperazinyl nitrogen. It is the first report of this compound being dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…The inset is the expansion of the spectra between two dashed lines, and the arrows point to the peaks previously assigned to sildenafil citrate. in Pronoton are consistent with those of Li et al 31 The presence of H-29 and H-30 at 2.83 and 3.72 ppm, respectively, in the 1 H NMR spectra and the two carbon signals at 60.2 ppm (C-29) and 58.0 ppm (C-30) observed in 13 C NMR spectra and distortionless enhancement by polarization transfer (DEPT) spectra 32 were the markers of this compound and were used to differentiate it from sildenafil and its other derivatives. Based on these analyses, it was further confirmed that the product Pronoton was adulterated with hydroxythiohomosildenafil.…”
Section: Identification Of Herbal Product -Pronotonsupporting
confidence: 93%
“…The inset is the expansion of the spectra between two dashed lines, and the arrows point to the peaks previously assigned to sildenafil citrate. in Pronoton are consistent with those of Li et al 31 The presence of H-29 and H-30 at 2.83 and 3.72 ppm, respectively, in the 1 H NMR spectra and the two carbon signals at 60.2 ppm (C-29) and 58.0 ppm (C-30) observed in 13 C NMR spectra and distortionless enhancement by polarization transfer (DEPT) spectra 32 were the markers of this compound and were used to differentiate it from sildenafil and its other derivatives. Based on these analyses, it was further confirmed that the product Pronoton was adulterated with hydroxythiohomosildenafil.…”
Section: Identification Of Herbal Product -Pronotonsupporting
confidence: 93%
“…By targeting the region of the spectra which will contain prominent features of the PDE-5 and PDE-5-like compounds, a single method can be used to ascertain the presence of multiple adulterants. Comparison of spectra obtained with the PDE-5 standards to literature spectra of PDE-5 inhibitors and their analogues not physically tested here confirms the presence of bands in this region [11][12][13][14][15]. KF31327, a PDE-5 like compound which does not share strong structural similarity to most PDE-5 inhibitors, also shows banding in this region, making this a highly effective method for detecting the presence of multiple PDE-5 inhibitors with a single test.…”
Section: Spectral Analysis and Data Processing Of Men's Specialty Prosupporting
confidence: 67%
“…In the last decade, various bioanalytical methods have been reported in the literature dedicated to the analysis of sildenafil [ 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 ]. An overview is presented in Table 5 [ 30 , 123 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , ...…”
Section: Analytical Strategies For the Determination Of Sildenafil In Pharmaceutical And Biological Matricesmentioning
confidence: 99%
“…In these reports, liquid chromatography coupled with mass spectrometry has become the technique of choice offering highly selective and sensitive determinations. Moreover, the LC-MS/MS technique has been considered as the “gold standard” for the screening and identification of erectile dysfunction drugs and their illegal analogues in adulterated food supplements and sexual performance enhancement products [ 182 , 183 , 184 ].…”
Section: Analytical Strategies For the Determination Of Sildenafil In Pharmaceutical And Biological Matricesmentioning
confidence: 99%
See 1 more Smart Citation